2020
DOI: 10.1177/0271678x20942397
|View full text |Cite
|
Sign up to set email alerts
|

A glucose-stimulated BOLD fMRI study of hypothalamic dysfunction in mice fed a high-fat and high-sucrose diet

Abstract: The hypothalamus is the central regulator of energy homeostasis. Hypothalamic neuronal circuits are disrupted upon overfeeding, and play a role in the development of metabolic disorders. While mouse models have been extensively employed for understanding the mechanisms of hypothalamic dysfunction, functional magnetic resonance imaging (fMRI) on hypothalamic nuclei has been challenging. We implemented a robust glucose-induced fMRI paradigm that allows to repeatedly investigate hypothalamic responses to glucose.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…Other studies have shown before that the chronic consumption of high fat diets leads to obesity and negatively affects brain function in terms of a worsen outcome after ischemic stroke 41 and that short-term high-fat and high-sucrose feeding impairs hypothalamic neuronal circuits, particularly in the arcuate, the ventromedial and the dorsomedial nucleus. 42 Visa versa, short-term exercise training effectively decreases insulin-stimulated brain glucose uptake in sedentary subjects with insulin resistance. 43 Moreover, insulin-induced CBF reduction may be an important determinant of cognitive decline observed in obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown before that the chronic consumption of high fat diets leads to obesity and negatively affects brain function in terms of a worsen outcome after ischemic stroke 41 and that short-term high-fat and high-sucrose feeding impairs hypothalamic neuronal circuits, particularly in the arcuate, the ventromedial and the dorsomedial nucleus. 42 Visa versa, short-term exercise training effectively decreases insulin-stimulated brain glucose uptake in sedentary subjects with insulin resistance. 43 Moreover, insulin-induced CBF reduction may be an important determinant of cognitive decline observed in obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Mice under isoflurane anesthesia were sacrificed by cardiac perfusion with cold PBS and then cold phosphate-buffered formaldehyde (Histolab, Askim, Sweden), and brains were cryosectioned into 20 µm slices [ 21 ]. Immunolabeling was carried out as detailed previously [ 23 ] with the primary antibodies: rabbit anti-allograft inflammatory factor 1 (Iba1, dilution 1:200; #019-19741, Fujifilm Wako, Japan; RRID:AB_839504), rat anti-CD11b (dilution 1:500; #MCA711, Bio-Rad, Sundbyberg, Sweden; RRID:AB_321292), anti-glial fibrillary acidic protein (GFAP) pre-tagged with AF488 (dilution 1:500; #53-9892-82, ThermoFisher Scientific, Göteborg, Sweden; RRID:AB_10598515), rabbit anti-glutamine synthetase (dilution 1:250; #ab176562, Abcam, Cambridge, UK; RRID:AB_2868472), anti-NeuN pre-tagged with AF488 (dilution 1:100; Cat# ab190195, Abcam; RRID:AB_2716282) and rabbit anti-doublecortin (dilution 1:500; #AB2253, Millipore-Merck, Darmstadt, Germany; RRID:AB_1586992). Secondary antibodies (dilution 1:500) were from ThermoFisher: AF568-conjugated goat anti-Rabbit IgG (#A-21069; RRID: AB_141416), AF568-conjugated goat anti-rat IgG (#A-21247; RRID:AB_141778) and AF488-conjugated goat anti-guinea-pig IgG (#A-11073; RRID:AB_2534117).…”
Section: Methodsmentioning
confidence: 99%
“…114 Finally, a very recent work described a robust experimental paradigm to assess real-time glucose-induced fMRI tasks in the mouse brain, and found that one-week high-fat and high-sucrose feeding impaired neuronal circuits in mice, particularly in the ARC, dorsomedial nucleus (DMN) and ventromedial nucleus + lateral hypothalamus (VMN+LH). 115…”
Section: Magnetic Resonance Imaging and Spectroscopy Of Cerebral Altementioning
confidence: 99%